The Moderation of Accounting Firm Size in Its Influence on Audit Quality During Covid’19 - Lili Sugeng Wiyantoro; Herlin Tundjung Setijaningsih (Jurnal Riset Akuntansi Terpadu, 2022)
Asymmetry of information between the management and the owners of the company, making management have opportunity to do some fraud. Asymmetry of information can be overcome with the audit process; the auditor is expected to detect the errors and fraud. Auditors who make mistakes in the audit process, have risk to getting lawsuits that called litigation risk. Additionally, auditor independence issues are a central position in the auditing literature. This problem is often sparked debate about audit quality, audit quality associated with audit tenure The purpose of this study was to examine the effect of litigation risk on audit quality, the effect size of audit firm as a moderating variable on the relationship between litigation risk and audit quality, the effect of audit tenure on audit quality, and effect size of audit firm as a moderating variable on the relationship between audit tenure and audit quality. The study used 117 data of financial statements of listed manufacturing companies in Indonesia Stock Exchange during the period 2019-2021 with a purposive sampling method. By using multiple regression with MRA in SPSS software. The results indicate that litigation risk has effect on audit quality, size of audit firm does not have effect on the relationship between litigation risk and audit quality, audit tenure has effect on audit quality, size of audit firm has effect on relationship between litigation risk and audit quality.